Mechanical Interpretation of Effects of Aeolian FineSands on Coal Fly Ash in Northern Shaanxi Province, China - Xin Wei; Chongyang Gao; Keyu Ai; Jun Zhao; Ling Xu (Advances in Civil Engineering)
The coal fly ash (CFA) is massively produced as a consequence of coal source residues in Northern Shaanxi Province, China. Since disposing the waste materials in mountainous gully widely distributed in the same area is one of the possibilities, the high compressibility and low strength of CFA become a severe problem for the stacking. The aeolian fine sands are close to Mu Us Desert, as the addition material was introduced to improve the mechanical behaviours of CFA. A series of oedometer and triaxial tests were performed on pure CFA, pure sands, and their mixtures containing 25%, 50%, and 80% of sands by weight, respectively. Test results were analyzed within the framework of critical state soil mechanics. With increasing sands content, normally consolidated lines (NCLs) and critical state lines (CSLs) of tested materials change in volume space as well as their compression or shearing paths. The mechanical parameters like Cc, Г, λ decrease as a result of increasing sands content. On the contrary, the M and ∅cs' increase with augmenting sands content. It is concluded that the aeolian sands can significantly decrease the compressibility of the CFA and increase its shear strength. These findings would be useful for the treatment of CFA, which is significant for solving environmental problems in northern Shaanxi Province.